PATHOTYPE PROFILE OF Xanthomonas oryzae pv. oryzae ISOLATES FROM THE RICE ECOSYSTEM IN JAVA - Suparyono Suparyono; Sudir Sudir; Suprihanto Suprihanto (Indonesian Journal of Agricultural Science, 2004)
At present, bacterial leaf blight of rice caused by Xanthomonas oryzae pv. oryzae is highly damaging to rice production in Indonesia as most of the existing commercial rice varieties are susceptible to the existing  pathotypes of the bacteria. To solve  such problems, varietal rotation should be based on information on the existence and dominance of local pathotypes in a particular rice ecosystem. To obtain this information, a total of 117 isolates of X. oryzae pv. oryzae, collected from West Java, Central Java, and Yogyakarta, were evaluated for their pathotype variation on five differential rice varieties during the dry season of 2000. When disease severity was < 10%, the reaction was classified as resistant (R) and when > 11%, was susceptible (S). The data indicated that 3.42% of the isolates were pathotype III, 12.82% were pathotype IV, and 83.76% were pathotype VIII. In West Java, the bacterial pathotypes III, IV, and VIII were 4.94%, 14.81%, and 80.25%, respectively. In low elevation areas, 4.94%, 9.88%, and 45.68% were pathotypes III, IV, and VIII, respectively and in medium areas, 4.94% were pathotypes IV and 34.57% were pathotype VIII. In Central Java, no pathotype III was found, while pathotypes IV and VIII were as much as 4.52% and 90.48%, respectively. In low elevation areas, no pathotypes III was recovered, and a total of 9.53% and 76.19% were identified as pathotypes IV and VIII, respectively, and in medium areas only pathotype VIII (14.29%) was identified. In Yogyakarta, pathotypes IV and VIII were found. In low elevation areas, 6.67% and 93.33% were pathotypes IV and VIII, respectively and in medium areas, 14.29% and 85.71% were pathotypes IV and VIII, respectively. The data indicated that variation in pathotype composition over different locations was obvious and locally specific resistant varieties to the disease are needed in the management of this important bacterial disease in rice.